Otimização do uso de sal de ervas e cloreto de potássio na substituição parcial do cloreto de sódio em corte e em linguiça de frango - Araújo, íris Braz da Silva (2012)
Sodium chloride is a component essential for the flavoring of food, particularly meat and its derivatives. However, too much can cause health problems to their consumers, such as hypertension. The objective of this research was partially replace sodium chloride by potassium chloride and a mixture of oregano (Origanum vulgare), basil (Ocimum basilicum) and rosemary (Rosmarinus officinalis), named Herbal Mix, initially in chicken breast fillets to determine an optimization interval of the variables to be tested in fresh sausages. Treatments were obtained using a Central Composite Rotational Design with three factors, resulting in 17 trials. Fillet of chicken breast with various flavors underwent Quantitative Descriptive Analysis for raising and quantify their sensory attributes. Subsequently, analyzes were carried out the physical parameters of quality (water holding capacity, cooking loss, shear force and color), to verify the influence of sodium chloride (NaCl), potassium chloride (KCl) and Herbal Mix on physical and sensory characteristics of meat. To check the possibility of further substitution of sodium chloride, found optimization intervals were studied in the development of fresh sausages, meat product to develop a low sodium content. The formulations of NaCl, KCl and Herbal Mix were obtained in a randomized mixture of three factors, the type simplex centroid, totaling 10 trials. The sausages were analyzed by sensory acceptance test (appearance, texture, flavor, global acceptance, purchase intention and intensity of salt), physical-chemical analysis (moisture, ash, proteins, lipids, pH and water activity) and physical (water holding capacity, cooking loss, shear force and color) to verify the influence of mixing of the quality factors of the samples. In the first study it was observed that, at 5% significance level, the response variables characteristic flavor, taste bitter and hardness influenced the statistical variables NaCl and Herbal Mix, while the attribute color gold was influenced by variables KCl and Herbal Mix . As for the physical parameters, only shear force of the treatments was influenced by variables, specifically KCl and Herbal Mix. To optimize a majority of the variables is chosen to optimize the following range, replacing initially 33% NaCl: 5-30 g / kg meat, 2-12 g / kg meat and 5-12 g / kg meat. Regarding the study of the reduction of optimized intervals showed that only the sensory analysis global acceptance and purchase intention influenced statistical variables. The physical-chemical properties, only the moisture and ash content were significantly influenced by the studied variables. None of the physical parameters was influenced by statistical factors. The experiment allowed a reduction of 20% sodium chloride without significant changes in quality of the sausage. With respect to experiment with chicken breast fillets, the use of potassium chloride and Herbal mix can replace sodium chloride up to 44,4%.